Enhanced Engraftment of a Very Low-Dose Cord Blood Unit in an Adult Haemopoietic Transplant by Addition of Six Mismatched Viable Cord Units - Stephen J. Proctor; Catherine E. Chapman; Rachel Sharples; Helen L. Lucraft; Jennifer Wilkinson; Jane Conn; Peter G. Middleton (Stem Cells International)
The report describes the feasibility of the addition of multiple viable HLA-mismatched unrelated cord blood units, to a low cell number matched unrelated cord, to assist clinical engraftment. An ablative stem cell transplant was performed in an adult with relapsed acute lymphoblastic leukaemia (ALL), using a single HLA-matched cord blood unit (mononuclear cell dose 0.8×107 ), supported by six mismatched cord blood units (one unit per 10 kg recipient weight). No adverse reaction occurred following the infusion of mismatched units and engraftment of the suboptimal-dose matched unit occurred rapidly, with no molecular evidence of engraftment of mismatched cords. Early molecular remission of ALL was demonstrated using a novel PCR for a mitochondrial DNA mutation in the leukaemic clone. The cell dose of the matched cord was well below that recommended to engraft a 70 kg recipient. We suggest that a factor or factors in the mismatched cords enhanced/supported engraftment of the matched cord.